An exploration of social media as a key site for the expression of post-racial politics - Bell, Joshua (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
This research sets out to examine colourblind racism in contemporary South Africa, specifically, as expressed on social media networks. In South Africa, a nation lauded for its transition from Apartheid to liberal democracy, racism still continues to exist. In the new democracy, racism continues in old, familiar forms but it has been suggested that racism also assumes new and emergent forms such as 'colourblind' racism. This is evident in recent controversies involving local public figures and their expressions of 'soft', 'colourblind' racism on Facebook. It is the new platforms and modes of racism unique to democratic South Africa which this thesis attempts to explore. Specifically, this study is framed by 'post-racialism', a concept developed by scholars globally to capture the suggestion that in liberal democratic societies across the world, racism continues with racial inequality now underpinned by an ideology of colourblindness as opposed to overt policies of segregation. Colourblindness denies the relevance of race as a collective issue, proposing instead that other social factors such as class are more pertinent in considerations of social inequality. The purpose of colourblind narratives may be identified as the reduction of racism to mere individual action, denying systemic white privilege and historical responsibility for reparation as well as preventing racially subjugated groups from critically interrogating racial power and privilege (Goldberg, 2015: 28-30). Post-racial theorists agree that the projection of colourblind politics which claims to no longer 'see race' has instead served to secure the normalisation of white privilege and black subjugation (Bonilla-Silva et al, 2004: 559-560). The purported existence of colourblind /post-racial racism and its impact requires exploration in the context of South Africa today. In expanding on the definition of racism, we are able to see that racism is an adaptive system of power that is able to reproduce and reconceptualise itself to changes within society. As modalities of racism have evolved, so have the platforms for its propagation. This research offers social media as a site of exploration for post-racial narratives. The case studies of Penny Sparrow, Helen Zille and Mabel Jansen are presented in this study as exemplars of post-racial liberalism, denial and exclusion. This research calls for the expansion of racial understanding so as to contest racial power structures as a continuing systemic issue in contemporary South Africa.
Keywords: Social media -- Political aspects -- South Africa; South Africa -- Politics and government -- 1994-; South Africa -- In mass media